2021
DOI: 10.1097/ta.0000000000003359
|View full text |Cite
|
Sign up to set email alerts
|

Critical care ultrasound in geriatric trauma resuscitation leads to decreased fluid administration and ventilator days

Abstract: BACKGROUND:Geriatric trauma populations respond differently than younger trauma populations. Critical care ultrasound (CCUS) can guide resuscitation, and it has been shown to decrease intravenous fluid (IVF), lower time until operation, and lower mortality in trauma. Critical care ultrasound-guided resuscitation has not yet been studied in geriatric trauma. We hypothesized that incorporation of CCUS would decrease amount of IVF administered, decrease time to initiation of vasopressors, and decrease end organ d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Studies [ 18 , 19 ] have shown that the traditional resuscitation care procedures are mainly focused on the rescue after the emergence of the problem, and the prognostic impact of the operations related to the assessment and prognosis of the disease, detailed management, and the interface of the resuscitation process is easily neglected, so there is a high risk of procedural confusion and delayed implementation of care measures in the rescue of HE patients, even if the health care workers are experienced and competent, which makes it difficult to ensure the effectiveness and orderliness of resuscitation. Optimizing the emergency care process means fully mobilizing the role of the nursing staff in the emergency department in the resuscitation procedure, when the emergency department receives the nursing staff to assess the patient's condition and immediately carry out life-saving measures as well as improve the success rate of emergency resuscitation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies [ 18 , 19 ] have shown that the traditional resuscitation care procedures are mainly focused on the rescue after the emergence of the problem, and the prognostic impact of the operations related to the assessment and prognosis of the disease, detailed management, and the interface of the resuscitation process is easily neglected, so there is a high risk of procedural confusion and delayed implementation of care measures in the rescue of HE patients, even if the health care workers are experienced and competent, which makes it difficult to ensure the effectiveness and orderliness of resuscitation. Optimizing the emergency care process means fully mobilizing the role of the nursing staff in the emergency department in the resuscitation procedure, when the emergency department receives the nursing staff to assess the patient's condition and immediately carry out life-saving measures as well as improve the success rate of emergency resuscitation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%